Successful breeding of striped snakehead (Channa striata) using artificial methods with stripping techniques in the Ciparanje inland fisheries area laboratory - Masyal, Muhamad Guntur; Arifat, Muhammad Rheno; Rohmah, Firli Aulia; Susilo, Bagus; Sudarto, Putri Berlianita; Zidni, Irfan (Acta Aquatica: Aquatic Sciences Journal, 2025)
Channa striata, or striped snakehead fish, is a freshwater fish with high economic value that is much needed by the community. The high demand for striped snakeheads still depends on the results of capture in nature. The high intensity of capture causes the availability of striped snakehead to be increasingly limited, but the cultivation of striped snakehead has not developed much in Indonesia. To anticipate these problems, this research aims to create striped snakehead cultivation techniques using artificial spawning methods with stripping techniques. The method used an experimental method with primary data obtained from direct observation and secondary data obtained from literature studies. The parameters observed were fecundity, FR (Fertilisation Rate), HR (Hatching Rate), and SR (Survival Rate). Fecundity results obtained from female striped snakehead were 1,578 grains, fertilization rate (FR) 88%, hatching rate (HR) 70.42%, and survival rate (SR) at the age of 7 days 94%. The results of the research show that snakehead fish (Channa striata) can be artificially spawned using a stripping technique using the GnRH (Gonadotropin Releasing Hormone) hormone which is useful for speeding up the ovulation process at a dose of 0.8 ml/kg for females and 0.6 ml/kg for males. Keywords: Cultivation; Experiments; Spawning